2016
DOI: 10.4300/jgme-d-16-00231.1
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Resident Autonomy During Family-Centered Rounds: A Qualitative Study of Resident, Hospitalist, and Subspecialty Physicians

Abstract: Background Family-centered rounds (FCR) have become a leading model for pediatric inpatient rounding. Several studies have examined effective teaching strategies during FCR, but none have focused on promoting resident autonomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…Indeed, as reported in one family‐centered rounds (FCR) study, senior residents often perceive decreased autonomy, and specific strategies can be employed to promote the autonomy of the resident physician in this team model. Setting clear expectations and defining responsibilities prior to the patient encounter are strategies that emerged from our results and are consistent with published FCR findings …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Indeed, as reported in one family‐centered rounds (FCR) study, senior residents often perceive decreased autonomy, and specific strategies can be employed to promote the autonomy of the resident physician in this team model. Setting clear expectations and defining responsibilities prior to the patient encounter are strategies that emerged from our results and are consistent with published FCR findings …”
Section: Discussionsupporting
confidence: 90%
“…This strategy begins with deductive coding, which integrates codes from relevant literature, followed by inductive coding, which involves the creation of de novo codes as the coder goes through the transcript line by line. For our purposes, an initial code list was derived from literature pertinent to swarming, including ED front‐end operations, ED process improvement, and FCR …”
Section: Methodsmentioning
confidence: 99%
“…Other strategies to promote autonomy as described by Beck et al [89] on Family-Centered Rounds (FCR) may be broken down to various phases of the FCR activity. Prior to the beginning of FCR, framing expectations and agreeing upon nonverbal signals were found to be helpful.…”
Section: Encouraging Autonomymentioning
confidence: 99%
“…After the FCR, promoting reflection and allowing the resident to reflect on how the rounds went is critical to improvement. Also allowing the resident to offer feedback to junior residents and medical students will promote the educational value of the FCR [89]. These steps outlined by Beck may be widely translatable to other activities within graduate medical education across specialties.…”
Section: Encouraging Autonomymentioning
confidence: 99%
“…2016;8:731-738. 9 This interview-based study identified strategies used by attending physicians to promote resident autonomy during family centered rounds.…”
Section: Topic 3: Professionalism and Learnersmentioning
confidence: 99%